International indigenous rights in Aotearoa New Zealand - Erueti, Andrew (Victoria University Press, 2017)
Over the past four decades, international indigenous rights have become a prominent aspect of international law and are now enshrined in the UN Declaration on the Rights of Indigenous Peoples. Yet, while endorsed by Aotearoa New Zealand in 2010, little remains known about how these standards came about, how the international movement that created them was established, and the implications of these standards on national reforms already protecting Māori rights. International Indigenous Rights in Aotearoa New Zealand seeks to answer these questions. This collection of essays places the Declaration in the context of New Zealand rights around such issues as Treaty settlements, mining policy and the status of Māori children. Crucially, it also asks how Māori can hold New Zealand to account against international indigenous rights.
Keywords: UNDRIP; government relations; human rights; iwi taketake; law; self-determination; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty claims

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism